EVALUASI ASPEK FUNGSI, ESTETIKA DAN AGRONOMIS TANAMAN TEPI JALAN DI JALAN IJEN KOTA MALANG - Murdaningsih Murdaningsih (AGRICA, 2010)
The research’s general objective was to study and evaluate; the function, aesthetic and agronomical aspects of side street plants at Ijen Street, Malang. Plant evaluation was needed to optimize plant effectiveness on the side of the streets, in realizing the city’s road concept that gives fluentness, safety, and improving environmental street visual quality. This is important especially for the side street plants to fulfil architectural, functional, and aesthetical values for the city environment. There was a lack of functional effectiveness at the traffic island as a site, caused by none continuation of tree planting. At one segment of the street the trees where physical and visual barries causing the inconvenience of concealing clear view. All segments of Ijen Street don’t have the function of a collision buffer. There was a windbreak function created by plant settlement with a corridor form. Plant function as sun control was accommodated in all of the street segments. Generally, the plant cover function by the plants has not been completed. The erosion control was accommodated by plant settlement at the traffic island in the street of Ijen. Plants function as noise control and identity was fulfilled with the existence of Rhoistonia reggia along the street. Overall the plants of Ijen Street have a lot of functions that help the site to improve environmental quality. Assessment of the esthetic aspect obtained from the election of plants types and a planting plan revealed that improvement to support the development function was required, according to of plants as agronomy value the existing plants can support plants function and add esthetical value.